2014
DOI: 10.1002/ece3.1097
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife road traffic accidents: a standardized protocol for counting flattened fauna

Abstract: Previous assessments of wildlife road mortality have not used directly comparable methods and, at present, there is no standardized protocol for the collection of such data. Consequently, there are no internationally comparative statistics documenting roadkill rates. In this study, we used a combination of experimental trials and road transects to design a standardized protocol to assess roadkill rates on both paved and unpaved roads. Simulated roadkill were positioned over a 1 km distance, and trials were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 42 publications
(141 reference statements)
1
49
1
4
Order By: Relevance
“…Transects were conducted on the N3 highway from Johannesburg to Durban along a total length of 431 km, driven four times a day every day (twice in each direction); teams were allocated to six shorter sections to ensure the whole distance was covered effectively. Once discovered, carcasses were removed from the road to avoid recounts (Collinson et al, 2014;Guinard et al, 2015). Road patrols took place from July 2011 to November 2014.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transects were conducted on the N3 highway from Johannesburg to Durban along a total length of 431 km, driven four times a day every day (twice in each direction); teams were allocated to six shorter sections to ensure the whole distance was covered effectively. Once discovered, carcasses were removed from the road to avoid recounts (Collinson et al, 2014;Guinard et al, 2015). Road patrols took place from July 2011 to November 2014.…”
Section: Data Collectionmentioning
confidence: 99%
“…Several studies have tried to identify and quantify bias in roadkill data collection (e.g., Slater, 2002;Santos et al, 2011) or develop standardized recording methods (e.g., Collinson et al, 2014), but to our knowledge none has tested the capacity of data from citizen science surveys to provide reliable roadkill data. In this study, we assessed the potential value of citizen science data for roadkill studies by comparing ad hoc data provided by citizen scientists (termed "occasional") to that of (1) road patrols by trained personnel (termed "road patrol") and (2) regular, informed observers working in the conservation field (termed "regular").…”
Section: Introductionmentioning
confidence: 99%
“…For example, four studies postulated that the way crossing structures are currently selected and even evaluated is biased and called for more effective mitigation selection and surveillance protocols [104,[125][126][127]. Similarly, a study conducted in a conservation area in South Africa revealed that the way roadkill surveys are undertaken can strongly influence road mortality estimates [128]. They identified that survey speed, time of day, and number of observers were all important factors to consider and highly recommended the use of standardized protocols.…”
Section: Survey Design and Mitigationmentioning
confidence: 99%
“…One transect was surveyed in one day in the morning session starting at 7:30 to around 11:30 am and in the afternoon session, it started from 14:00 to around 18:00 pm. The vehicle was driven at 20 kph or less with stopping to take records of each bird or group of birds encountered (Collinson et al, 2014;Mahulu et al, 2015). A binocular was also used to clearly identify birds.…”
Section: Data Collectionmentioning
confidence: 99%
“…This is because the periodic road maintenance entails habitat destruction and population fragmentation (Senzota, 2012). As a result, its effects on birds can represent high mortalities of birds on roads passing through protected areas (Ramp et al, 2006;Mkanda and Chansa, 2011;Collinson et al, 2014). For the period between 2013 and 2015, the impact of roads on bird mortality was reported to be 50% in Tarangire-Manyara Ecosystem in Tanzania (Kioko et al, 2015).…”
Section: Introductionmentioning
confidence: 99%